2020
DOI: 10.1186/s12891-020-03262-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects and safety of the combination of platelet-rich plasma (PRP) and hyaluronic acid (HA) in the treatment of knee osteoarthritis: a systematic review and meta-analysis

Abstract: Background: Studies have shown that the combined application of hyaluronic acid (HA) and platelet-rich plasma (PRP) can repair degenerated cartilage and delay the progression of knee osteoarthritis (KOA). The purpose of this study was to explore the efficacy and safety of the intra-articular injection of PRP combined with HA compared with the intra-articular injection of PRP or HA alone in the treatment of KOA. Methods: The PubMed, Cochrane Library, EMBASE and China National Knowledge Infrastructure (CNKI) dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 38 publications
2
75
0
4
Order By: Relevance
“…This synergistic effect mainly changes the role of inflammatory cytokines in the process of chondrocyte degeneration through specific mediators (CD44, TGF-βRII), thereby promoting cartilage regeneration and inhibiting the inflammatory response 15 . Recent meta-analysis showed that intraarticular injection of PRP combined with HA has a unique advantage in the long-term relief of pain in patients with knee OA, which may suggest that the combination therapy may be a better treatment for patients with long-term knee pain in the future 38 .…”
Section: Discussionmentioning
confidence: 99%
“…This synergistic effect mainly changes the role of inflammatory cytokines in the process of chondrocyte degeneration through specific mediators (CD44, TGF-βRII), thereby promoting cartilage regeneration and inhibiting the inflammatory response 15 . Recent meta-analysis showed that intraarticular injection of PRP combined with HA has a unique advantage in the long-term relief of pain in patients with knee OA, which may suggest that the combination therapy may be a better treatment for patients with long-term knee pain in the future 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it revealed that PRP combined with HA did provide better overall clinical improvement than HA in terms of symptom-function improvement at every follow-up visit or in terms of duration of effect. 29 In this study, the improvement of inflammation and joint function and pain for KOA was investigated in depth. Therefore, the goal of this study was to evaluate the effectiveness and explore the therapeutic mechanisms of PRP combined with HA as a treatment for KOA.…”
mentioning
confidence: 99%
“…There were no other differences between the two groups, indicating that the combined approach could be the method of choice for long-term pain relief in OA patients [ 87 ]. A meta-analysis by Zhao et al demonstrated the greater benefit of combined PRP and HA injection compared to single therapy for both pain scores at 6 months’ follow-up and function at 12 months’ follow-up [ 88 ]. Superior benefits of the combined therapy were corroborated in a systematic review and meta-analysis by Karasavvidis et al, who concluded that patients treated with a combination of PRP and HA had better clinical results for both pain and function (measured by VAS at 3, 6, and 12 months’ follow-ups and 12-month WOMAC physical function and stiffness score) compared to patients treated with HA only [ 89 ].…”
Section: Intra-articular Injectionsmentioning
confidence: 99%